Literature Review of Turkish Sportsmen in Terms of ACTN3 R577X Polymorphism - ULUCAN, KORKUT (AVES PRESS LTD, 2016)
The effect of genes on individual athletic performance is accepted; however, the extent of their effects remains elusive. To date, many studies on different genomic regions that are considered to have an effect on human athletic performance and sportsmen in different types of sports, such as football, basketball, judo, and wrestling, have been conducted. However, the number of these studies with Turkish players as subjects is not adequate. This literature review aimed to collate the results of alpha-actinin-3 (ACTN3) R577X polymorphisms of Turkish athletes after an extensive literature survey. After the survey, we could reach 518 players, including football, basketball, and wrestling players. Of these, 234 were RR (45%), 207 (40%) were RX, and the rest were XX. Power and sprinter R allele counts were 665 (64%), and the endurance allele count was 371 (36%). According to the obtained data, the number and percentage of RR+RX genotypes and R allele were higher than those of XX genotype and X allele. We consider that this first report will be an informative source of information for Turkish players in the terms of ACTN3 R577X polymorphism and Turkish sportsman and will be a valuable guide for new researches.
Keywords: Sports; genetics; predisposition to sports; ACTN3; Turkey